Effect of the Chemical Composition of Miso (Japanese Fermented Soybean Paste) Upon the Sensory Evaluation. (24th July 2019) - Wang, Shuo; Tamura, Takehiro; Kyouno, Nobuyuki; Liu, Xiaofang; Zhang, Han; Akiyama, Yoshinobu; Yu Chen, Jie
Abstract: Miso is a fermented soybean paste that is consumed in the traditional Japanese diet. Understanding the effects of chemical characteristics on miso sensory evaluation enables the classification of miso quality. This study investigated the chemical composition of 26 products from the Akita Prefectural Miso Competition in 2016 and 2017 to determine correlations with their sensory evaluation. The results showed that external appearance contributed significantly to the quality classification, with a reddish-brown color considered more acceptable in the Akita area. Increase in acids (except lactic acid) and amino acid contents were also responsible for enhanced sensory quality. Furthermore, the results from principal component regression showed that the presented measurements contribute to providing an alternative objective evaluation of these food products.